MODIFIKASI EXTERNAL PUMP DRIVE L135M2905101 PADA PRESSURE SUPPLY SYSTEM HELIKOPTER AIRBUS EC-135 P3 SEBAGAI ALAT BANTU PERAWATAN DI HANGAR 3 SEKOLAH TINGGI PENERBANGAN INDONESIA - Hanris Lukkas Adi Putra; Zulham Hidayat; Haryadi (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
In maintenance process of Airbus Helicopter EC-135 P3 based on Master Servicing Manual there are several type of maintenance procedure which there are tasks like leakage test hydraulic power supply, pressure test, and bleeding. One of the tools used on this task is external pump drive. During this time the implementation of maintenance using tools from Airbus Helicopter Indonesia and there are some deficiency that is rotating speed does not reach 5145 rpm as needed hydraulic power system. Therefore, then the writer will modify the tool which has a rotating speed of 5145 rpm. General description for consideration external pump drive, the writer want to use a timing belt transmission system by utilizing accuracy when turning. The modification design stage that was undertaken was first determining the driving motor proceed with designing the timing belt, the third stage is making the internal gear drive the drive shaft, followed by the stages of making the timing belt transmission housing and determining the bearings. The results of this modification are expected to be beneficial for STPI especially Unit Perawatan Pesawat Udara to assists the process of leakage test, pressure test, and bleeding in the hydraulic power system